La fiscalidad sobre el consumo en una ciudad mediterránea - Lluís Sales i Favà (Medievalista)
This article focuses on the so-called Lleuda de Mediona, a tax on the sale of foods, raw materials and cloth applied in the city of Barcelona during pre-Modern times. With the use of unpublished sources of litigious and/or regulatory nature, the origin and evolution of the tax between the thirteenth and fourteenth centuries are discussed. Two separate sections describe special charges that were directly linked to the Lleuda: the socalled mesuratge, that affected the marketing of olive oil; and the quint of cuiram, applied to the trade of leather and cochineal. The latter were commodities usually imported from the Islamic regions of the southern shore of the Mediterranean. The article underlines the importance of these products in the urban economy of the period. Finally, this study describes some features about the origins of the Lleuda and its mechanics.